Configural Perspectives on Urban Talent Ecology and Talent Competitiveness: A Dual Analysis Using GQCA and fsQCA - Peng Jiang; Zhaohu Dong; Ran Zhang; Yingchun Song (Systems)
Talent significantly influences urban technological innovation and sustainable economic development. Enhancing urban talent competitiveness (UTC) necessitates a systemic perspective on upgrading and optimizing the combination of both tangible and intangible resources, such as economic vitality, livability, and social harmony, which is a typical configurational issue. This paper utilizes empirical data from 96 Chinese cities and applies an innovative grey quantitative comparative analysis (GQCA) method to investigate the impact and mechanisms of different urban talent ecology (UTE) on talent competitiveness. The findings reveal that there are no bottleneck factors constraining UTC within the sample, interactions, and couplings among six urban talent elements that generated 30 distinct UTEs. By calculating the possibility of each UTE achieving talent competitiveness, it was found that 16 UTEs, characterized by vibrant business-led development, comprehensive development and integrated leadership, regional development leadership, and economy-led international innovation, lead to high UTC. Conversely, 14 UTEs result in low UTC. These findings were further validated through fuzzy set qualitative comparative analysis (fsQCA) for robustness testing. Finally, the study offers policy recommendations for urban talent strategies from both short-term and long-term perspectives.